Soil fauna-microbial interactions shifts fungal and bacterial communities under a contamination disturbance - Correa-Garcia, Sara; Corelli, Vincenzo; Tremblay, Julien; Dozois, Jessica Ann; Mukula, Eugenie; Séguin, Armand; Yergeau, Etienne (PLOS ONE, 2023)
The aim of this study was to determine whether the soil faunal-microbial interaction complexity (SFMIC) is a significant factor influencing the soil microbial communities and the willow growth in the context of PAH contamination. The SFMIC treatment had eight levels: just the microbial community, or the microbial community with nematodes, springtails, earthworms and all the possible combinations. SFMIC affected the height and biomass of willows after eight weeks or growth. SFMIC affected the structure and the composition of the bacterial, archaeal and fungal communities, with significant effects of SFMIC on the relative abundance of fungal genera such as Sphaerosporella, a known willow symbiont during phytoremediation, and bacterial phyla such as Actinobacteriota, containing many polycyclic aromatic hydrocarbons (PAH) degraders. These SFMIC effects on microbial communities were not clearly reflected in the community structure and abundance of PAH degraders, even though some degraders related to Actinobacteriota and the diversity of Gram-negative degraders were affected by the SFMIC treatments. Over 95% of PAH was degraded in all pots at the end of the experiment. Overall, our results suggest that, under our experimental conditions, SFMIC changes willow phytoremediation outcomes.